One-pot process for the conversion of aroyl chlorides to acyl thioureas - Ramana, Chepuri V.; Senthilkumar, B. (WO2014087431A1, WO2014087431A8, 2013)
The present invention disclose an improved one pot process for synthesis of acyl thioureas of formula (I), with yield greater than 80%, from aroyl chlorides of formula (I) wherein, R′ is an aryl or a heteroarylene group substituted with one or more groups selected from hydrogen, alkyl, alkylene, alkynyl, alkoxy, alkenyloxy, halo, hydroxyl, nitro, amino, carboxyl, ester, halogenated hydrocarbon or an aryl or heteroaryl; R″ and R′″ are selected independently from hydrogen, alkyl, alkylene, alkynyl, alkoxy, alkenyloxy, halo, hydroxyl, nitro, amino or halogenated hydrocarbon.

Optimization of the anti-cancer activity of the phosphatidylinositol-3 kinase pathway inhibitor PITENIN-1: switching thiourea with 1,2,3-triazole - Kommagalla, Yadagiri; Cornea, Sinziana; Riehle, Robert; Torchilin, Vladimir; Degterev, Alexei; Ramana, Chepuri V. (Medchemcomm, 2014)
We previously reported encouraging in vitro and in vivo anti-cancer activity of N-((3-chloro-2-hydroxy-5-nitrophenyl)carbamothioyl) benzamide (termed PITENIN-1). In the current work, we describe the structure-activity relationship study of the PIT-1 series, based on the replacement of a central thiourea unit with 1,2,3-triazole, which leads to increased liver microsomal stability, drug likeness and toxicity towards cancer cells.

Oxone-acetone mediated syn-dioxygenation of benzo-fused olefins - Phatake, Ravindra S.; Ramana, Chepuri V. (Tetrahedron Letters, 2015)
The oxone-acetone combination well established for olefin epoxidation has been demonstrated to be a practical reagent for the syn-dioxygenation (resulting in 1,3-dioxolanes) of indenes and dihydronaphthalenes. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Dihydronaphthalene; Dioxygenation; Indene; Oxone

Oxone-acetone mediated wacker-type oxidation of benzo-fused olefins - Phatake, Ravindra S.; Ramana, Chepuri V. (Tetrahedron Letters, 2015)
Herein we disclose a novel application of the oxone-acetone combination for the Wacker-type oxidation of indenes and dihydronaphthalenes leading, respectively, to indan-2-ones and 2-tetralones. The amount of the base employed in the reaction seems to switch the reaction path from dioxygenation to Wacker-type oxidation. Control experiments suggest that the reaction is not proceeding via the epoxide route and also that there is no role of trace amounts of metals present in the reagents on the current oxidation. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Dihydronaphthalene; Indene; Oxone; Wacker oxidation

O-Quinone methides via oxone-mediated benzofuran oxidative dearomatization and their intramolecular cycloaddition with carbonyl groups: an expeditious construction of the central tetracyclic core of integrastatins, epicoccolide A, and epicocconigrone A - More, Atul A.; Ramana, Chepuri V. (Organic Letters, 2016)
The intramolecular cycloaddition of o-quinone methides (o-QMs) with a carbonyl group has been envisaged and executed successfully in the context of constructing the complex and rare [6,6,6,6]-tetracyclic core found in the integrastatins, epicoccolide A, and epicocconigrone A. These transient o-QMs were generated easily from the oxidative dearomatization of the corresponding C2-(aryl)benzofuran by employing Oxone in acetone-water at rt. The subsequent cydoaddition with the carbonyl (or conjugated olefin) present on the C2-aryl group was spontaneous.